ANALISIS PENENTUAN HARGA JUAL KORAN PADA KALTIM POST DI SAMARINDA - MARNO -; SITI MASYITHOH; MUHAMMAD IKBAL (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
This research is directly implemented in Samarinda Kaltim Post, located in the city of Samarinda is an industry engaged in a newspaper. The company set the selling price based on the purchase price of the issuer plus the desired profit company. The problems in this thesis is whether the determination of the selling price based on cost-plus pricing approach to the concept of total cost (total cost) is lower or higher than that of determining the selling price set by the company? In accordance with the above problems, the purpose of this paper is to compare the selling price established by the company with the count using cost-plus pricing approach to the concept of total cost (total cost). The analytical tool used in this study is a cost-plus pricing approach to the concept of cost (total cost). First determine the cost of production. The second determines the total cost. Third ROI calculation. Fourth calculation of expected profit. Furthermore, the calculation of mark up the first and last sale price calculation. The calculations show Kaltim Post newspaper selling price based on the cost-plus pricing approach Rp 3904.02, while according to the company amounted to Rp 4000, so there is a difference of Rp 95.98 Thus it is known that the sales price based newspaper cost-plus pricing approach to the concept of total cost (total cost) is lower than the selling price set by the company.Keywords: Cost-Plus Pricing, Total Cost